2013
DOI: 10.1186/1476-069x-12-77
|View full text |Cite
|
Sign up to set email alerts
|

State and national household concentrations of PM2.5 from solid cookfuel use: Results from measurements and modeling in India for estimation of the global burden of disease

Abstract: BackgroundPrevious global burden of disease (GBD) estimates for household air pollution (HAP) from solid cookfuel use were based on categorical indicators of exposure. Recent progress in GBD methodologies that use integrated–exposure–response (IER) curves for combustion particles required the development of models to quantitatively estimate average HAP levels experienced by large populations. Such models can also serve to inform public health intervention efforts. Thus, we developed a model to estimate nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
124
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 27 publications
16
124
3
1
Order By: Relevance
“…Separate estimates by sex were 2.30 (1.73, 2.06) for women and 1.90 (1.15, 3.13) for men. 3 Causal inference is supported by these findings, consistency (almost all studies reported increased risk, though not all significant), positive intervention-based findings (7), exposure-duration evidence, analogous evidence from smoking, and biological plausibility.…”
Section: Chronic Obstructive Pulmonary Diseasesupporting
confidence: 58%
“…Separate estimates by sex were 2.30 (1.73, 2.06) for women and 1.90 (1.15, 3.13) for men. 3 Causal inference is supported by these findings, consistency (almost all studies reported increased risk, though not all significant), positive intervention-based findings (7), exposure-duration evidence, analogous evidence from smoking, and biological plausibility.…”
Section: Chronic Obstructive Pulmonary Diseasesupporting
confidence: 58%
“…The use of biomass fuel combustion in most of the Himalayan region is a significant part of the energy need, and its use escalates during winter season (Parikh 2011). Emissions from biomass and fossil fuel (PAHs and other organic compounds), and climate variables would impact the composition of OCs associated with ambient PM which may differ from that observed from other regions (Gelencsér 2004;Liu et al 2009;Balakrishnan et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…3 billion people worldwide continuing to use solid fuel for cooking or heating leading to dramatic indoor air pollution, with concentrations of particulate matter that are often 30 times higher than the air quality guidelines of the World Health Organization. 2,3 Although abundant epidemiologic evidence suggests that chronic biomass smoke exposure is associated with COPD, [4][5][6][7] results from stove trials have been less consistent. Although an intention-to-treat (ITT) analysis from the Randomized Exposure Study of Pollution Indoors and Respiratory Eff ects (RESPIRE) in Guatemala did not identify a difference in lung function decline in young adult women receiving a chimney stove compared with open fire users over 12 to 18 months of follow-up, 8 an exposure-response analysis showed that higher exhaled breath carbon monoxide (EB co ) was associated with lower FEV 1 .…”
mentioning
confidence: 99%